Infectious mononucleosis as a risk factor for depression: A nationwide cohort study - Vindegaard, Nina; Petersen, Liselotte V.; Lyng-Rasmussen, Bodil Ingrid; Dalsgaard, Søren; Benros, Michael Eriksen (Brain, Behavior, and Immunity, 2021)
•Infectious mononucleosis is often associated with prolonged fatigue.•The association with depression was unclear since large-scale studies were lacking.•This prospective cohort study included 12,510 individuals with the infection.•Infectious mononucleosis was associated with a 40% increased risk for depression.•The increased risk was significant to the period one year or later after the infection. Infectious mononucleosis is a clinical diagnosis characterized by fever, sore throat, lymph node enlargement and often prolonged fatigue, most commonly caused by Epstein-Barr virus infection. Previous studies have indicated that infectious mononucleosis can be followed by depression; however, large-scale studies are lacking. We used nationwide registry data to investigate the association between infectious mononucleosis and subsequent depression in this first large-scale study. Prospective cohort study using nationwide Danish registers covering all 1,440,590 singletons born (1977–2005) in Denmark by Danish born parents (21,830,542 person-years’ follow-up until 2016); where 12,510 individuals had a hospital contact with infectious mononucleosis. The main outcome measures were a diagnosis of major depressive disorder (ICD-8: 296.09, 298.09, 300.4; ICD-10: F32) requiring hospital contact. Infectious mononucleosis was associated with a 40% increased hazard ratio (HR) for a subsequent depression diagnosis in the fully adjusted model (HR: 1.40, 95% CI: 1.26–1.56;n = 358), when compared to unexposed individuals. The increased risk of being diagnosed with depression was significant to the periods one to four years after the infectious mononucleosis diagnosis (HR: 1.40, 95% CI: 1.17–1.67;n = 121) and ≥ five years (HR: 1.40, 95% CI: 1.22–1.61;n = 207). We did not find any differences according to age (p = 0.61) nor sex (p = 0.30). In this largest study to date, infectious mononucleosis in childhood or adolescence was associated with an increased risk of a subsequent depression. Our findings have important clinical implications and identifies youth with infectious mononucleosis as a group at high risk of later depression in young adulthood.